Website Lapak Desa Untuk Promosi Dan Pemasaran Produk UMKM Di Desa Sambirejo Timur, Kabupaten Deli Serdang - Ihsan Lubis; Husni Lubis; Halimatussa’diah; Maxi L Hutahaean; Marcho M Hutahaean; Ahmad Daffa; Yuli Artika; Salsabila (CV. Multi Kreasi Media, 2023)
East Sambirejo Village is a village in Deli Serdang district. The village has many MSME businesses that are managed conventionally. This makes product marketing's reach limited. In this digital era, the internet is one of the most effective and efficient marketing media because it has a wide market reach and is more cost-effective. Based on this, this activity was carried out to improve the marketing of MSME products in East Sambirejo Village. The expected results of this activity are to produce a website that the village community can use to promote existing products in the village and also sell MSME products online.